THE IMPLEMENTATION OF COOPERATIVE LEARNING: STUDENT TEAMS-ACHIEVEMENT DIVISIONS TECHNIQUE IN TEACHING READING COMPREHENSION - Sophia Fithri Al-Munawwarah (Journal of English and Education, 2013)
This study aims to investigate the benefits of implementing cooperative learning with STAD technique in teaching reading comprehension and the students’ responses toward the implementation of STAD technique. This study was conducted based on the assumption that STAD technique can be a recommended technique in teaching English for EFL students (Wichadee, 2006). The study employed case study approachand the data were collected through observation, interview, written documents, and dependent t-test to gain relevant data.The research findings of this study discover six benefits of STAD technique, as follows: (1) engaging students in reading activity; (2) increasing students’ motivation to practice actively in the learning process; (3) helping students to solve their problems in comprehending the texts; (4) developing students’ social skill; (5) creating enjoyable learning atmosphere; and (6) enhancing students’ reading comprehension skills. In addition, the students’ responses toward the implementation of STAD technique in teaching reading were positive. Thus, it is recommended that STAD technique be implemented in teaching reading comprehension. Keywords:       Cooperative Learning, reading comprehension, STAD technique